An Investigation into the Role of Coping in Preventing Depression Associated with Perfectionism in Preadolescent Children - Dry, Silja M.; Kane, Robert Thomas; Rooney, Rosanna M. (Frontiers in Public Health, 2015)
The relationships between self oriented and socially prescribed perfectionism and maladaptive and adaptive coping strategies and their collective impact on depression symptoms were examined in the context of a randomised controlled universal trial of the Aussie Optimism Positive Thinking Skills intervention. 541 children aged 8 to 12 completed a battery of self reports, of which responses for measures of depression symptoms, perfectionism and coping strategies were examined for the purposes of this study. Structural equation modelling tested whether coping mediated the effects of perfectionism on depression indicated that socially prescribed perfectionism had both a direct and indirect relationship with depression symptoms through a moderate association with maladaptive coping. Implications for prevention of depression were discussed and recommendations for future research were proposed.